Shear Lag in Slotted Welded Steel CHS Connections - ساحللي, سامر (Latakia University Journal -Engineering Sciences Series, 2024)
The Shear Lag Phenomenon plays a significant role in the structural behavior of steel element connections, affecting their strength and performance. This study investigates the impact of shear lag on the resistance of welded connections when subjected to severe forces, particularly in the case of slotted steel CHS (Circular Hollow Sections) pipes welded to steel plates (Gusset plates). This study contributes to highlighting the importance of this phenomenon to consider its effect according to the European Code (EC3), which explicitly ignores its impact on various types of connections, especially welded ones. The research evaluates the influence of various factors such as the overlap length (connection length) and the diameter of the connected steel pipes exposed to central concentrated forces on the evolution of the shear lag phenomenon and its consequences on the proposed connection's resistance and durability. This is achieved through analysis using the Component-based Finite Element Method (CBFEM), adopted from the European Code for the analysis and design of steel connections. Furthermore, the research aims, through numerical analytical study, to develop a relationship to calculate the value of the shear lag coefficient for inclusion in the equations used to check these connections according to the European Code. Additionally, it provides some explanations regarding the impact of the mentioned factors (connection length and diameter of steel pipes) on the shear lag coefficient to assist in selecting the appropriate geometric dimensions of the mentioned connections to ensure achieving the desired efficiency and performance within the framework of structural safety procedures in steel structures.